1999
DOI: 10.1007/bf02508414
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and biotechnological aspects of obtaining medicinal preparations fromRhodiola Rosea L. (A review)

Abstract: By now, there are about 300 medicinal plants successfully used in medical practice. Moreover, recent years showed a steady tendency for extending this class.Obtaining phytopreparations always involves extraction of the biologically active substances, followed by their separation and purification using various technological methods. One of the main negative factors, introducing instability in the manufacture of phytopreparations, is an irregular character of the supply of raw materials for their production. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…rosea rhizomes with roots can be up to 3.5 kg [16,40]. In Plewiska near Poznań, the fresh weight of the raw material after six years of growing from seeds reached up to 1.7 kg [29], and similarly in Finland -more than 2 kg [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rosea rhizomes with roots can be up to 3.5 kg [16,40]. In Plewiska near Poznań, the fresh weight of the raw material after six years of growing from seeds reached up to 1.7 kg [29], and similarly in Finland -more than 2 kg [3].…”
Section: Discussionmentioning
confidence: 99%
“…The most important biologically active constituents are phenolics [14]. There are mainly: phenylpropanoids (rosavin, rosin and rosarin), phenyletanoids (salidroside and p-tyrosol), flavonoids, proanthocyanidins as well as tannins [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] (-)-Rosiridol itself also occurs in the leaves of Cunila spicata (Lamiaceae) [4] and in the petals of the rose Rosa damascena. [5] (-)-Rosiridin (2) is the β-glucosylated analogue of (-)-rosiridol (1) [6] and has recently been identified as an inhibitor of monoamine oxidase B (MAO B), which is involved in neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 98%
“…In Poland, roseroot grows in the Giant Mountains, Babia Góra, Tatra and Bieszczady Mountains [4][5][6]. For centuries, rhizomes of this species, also known as golden root, arctic root, and Hongjingtian in Chinese, have been an important raw material in folk medicine of Scandinavia, Russia, Mongolia, and China [7][8][9][10]. Traditional use was associated with the adaptogenic properties of this taxon.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional use was associated with the adaptogenic properties of this taxon. In the last decades, many research studies have found that roseroot increases mental and physical strength as well as it shows anti-stress, cardioprotective, antioxidative, immunomodulatory, and anticancer activities [7,[11][12][13][14]. The above-described features of Rh.…”
Section: Introductionmentioning
confidence: 99%